Germline deletion of pantothenate kinases 1 and 2 reveals the key roles for CoA in postnatal metabolism. - Matthew Garcia (Public Library of Science (PLoS), 2012)
Pantothenate kinase (PanK) phosphorylates pantothenic acid (vitamin B(5)) and controls the overall rate of coenzyme A (CoA) biosynthesis. Pank1 gene deletion in mice results in a metabolic phenotype where fatty acid oxidation and gluconeogenesis are impaired in the fasted state, leading to mild hypoglycemia. Inactivating mutations in the human PANK2 gene lead to childhood neurodegeneration, but Pank2 gene inactivation in mice does not elicit a phenotype indicative of the neuromuscular symptoms or brain iron accumulation that accompany the human disease. Pank1/Pank2 double knockout (dKO) mice were derived to determine if the mild phenotypes of the single knockout mice are due to the ability of the two isoforms to compensate for each other in CoA biosynthesis. Postnatal development was severely affected in the dKO mice. The dKO pups developed progressively severe hypoglycemia and hyperketonemia by postnatal day 10 leading to death by day 17. Hyperketonemia arose from impaired whole-body ketone utilization illustrating the requirement for CoA in energy generation from ketones. dKO pups had reduced CoA and decreased fatty acid oxidation coupled with triglyceride accumulation in liver. dKO hepatocytes could not maintain the NADH levels compared to wild-type hepatocytes. These results revealed an important link between CoA and NADH levels, which was reflected by deficiencies in hepatic oleate synthesis and gluconeogenesis. The data indicate that PanK1 and PanK2 can compensate for each other to supply tissue CoA, but PanK1 is more important to CoA levels in liver whereas PanK2 contributes more to CoA synthesis in the brain.